From Isolation towards Integration - de Groot, S.W (d565f92b-9327-4746-8929-f00d08dc48ca, 1977)
From Isolation towards Integration was originally published in Dutch as Volume 41 (1963) in the series Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde.